Reducing inappropriate outpatient antibiotic prescribing: normative comparison using unblinded provider reports. Issue 1 (13th February 2019) - Milani, Richard V; Wilt, Jonathan K; Entwisle, Jonathan; Hand, Jonathan; Cazabon, Pedro; Bohan, Jefferson G
Abstract : Importance: Antibiotic resistance is a global health issue. Up to 50% of antibiotics are inappropriately prescribed, the majority of which are for acute respiratory tract infections (ARTI). Objective: To evaluate the impact of unblinded normative comparison on rates of inappropriate antibiotic prescribing for ARTI. Design: Non-randomised, controlled interventional trial over 1 year followed by an open intervention in the second year. Setting: Primary care providers in a large regional healthcare system. Participants: The test group consisted of 30 primary care providers in one geographical region; controls consisted of 162 primary care providers located in four other geographical regions. Intervention: The intervention consisted of provider and patient education and provider feedback via biweekly, unblinded normative comparison highlighting inappropriate antibiotic prescribing for ARTI. The intervention was applied to both groups during the second year. Main outcomes and measures: Rate of inappropriate antibiotic prescription for ARTI. Results: Baseline inappropriate antibiotic prescribing for ARTI was 60%. After 1 year, the test group rate of inappropriate antibiotic prescribing decreased 40%, from 51.9% to 31.0% (p<0.0001), whereas controls decreased 7% (61.3% to 57.0%, p<0.0001). In year 2, the test group decreased an additional 47% to an overall prescribing rate of 16.3%, and the control group decreased 40% to a prescribing rate of 34.5% after implementation of the same intervention. Conclusions and relevance: Provider and patient education followed by regular feedback to provider via normative comparison to their local peers through unblinded provider reports, lead to reductions in the rate of inappropriate antibiotic prescribing for ARTI and overall antibiotic prescribing rates.